The myth of the “street artist”:: a brief note on terminology - Bengtsen, Peter (SAUC - Street Art and Urban Creativity (repository), 2017)
Among researchers within the field of street art studies, a discussion crops up repeatedly, both in publications and in conversations at conferences. It is usually set off by someone asking one or more interrelated questions, including the following: How do we define street art? Is it still street art if it is shown in a gallery or museum? And what, precisely, makes someone a street artist?